The UMKM Online Advantage: Linking Digital Strategies to Enhanced Consumer Purchase Intentions - Mas'ud, Anis Anshari; Tenriyola, Andi Putri (Universitas Sulawesi Barat, 2025)
This study explores the online advantage Micro, Small, and Medium Enterprises (UMKM) within the culinary sector can achieve by effectively linking their diverse digital strategies to enhanced consumer purchase intentions. An empirical approach was employed, involving surveys with consumers who actively engage with culinary UMKMs through their various digital platforms. Data collected via questionnaires were meticulously analyzed to elucidate the intricate interplay between different facets of digital engagement—ranging from information accessibility to interactive communication—and the evolution of consumer interest in culinary offerings. The findings consistently indicate that thoughtfully implemented digital strategies, which extend beyond a mere online presence, positively influence consumer purchase intention. This demonstrates a clear and attainable online advantage for these enterprises in a competitive digital landscape. The study concludes that the adoption of dynamic and contextually relevant digital strategies, especially those prioritizing entertaining and emotionally resonant content, provides a considerable online advantage for culinary UMKMs seeking to stimulate consumer purchase intentions and cultivate lasting brand loyalty